Transcriptomic Analysis of Chronic Hepatitis B and C and Liver Cancer Reveals MicroRNA-Mediated Control of Cholesterol Synthesis Programs - Sara R. Selitsky (American Society for Microbiology, 2015)
ABSTRACT Chronic hepatitis B (CHB), chronic hepatitis C (CHC), and associated hepatocellular carcinoma (HCC) are characterized by cholesterol imbalance and dyslipidemia; however, the key regulatory drivers of these phenotypes are incompletely understood. Using gene expression microarrays and high-throughput sequencing of small RNAs, we performed integrative analysis of microRNA (miRNA) and gene expression in nonmalignant and matched cancer tissue samples from human subjects with CHB or CHC and HCC. We also carried out follow-up functional studies of specific miRNAs in a cell-based system. These studies led to four major findings. First, pathways affecting cholesterol homeostasis were among the most significantly overrepresented among genes dysregulated in chronic viral hepatitis and especially in tumor tissue. Second, for each disease state, specific miRNA signatures that included miRNAs not previously associated with chronic viral hepatitis, such as miR-1307 in CHC, were identified. Notably, a few miRNAs, including miR-27 and miR-224, were components of the miRNA signatures of all four disease states: CHB, CHC, CHB-associated HCC, and CHC-associated HCC. Third, using a statistical simulation method (miRHub) applied to the gene expression data, we identified candidate master miRNA regulators of pathways controlling cholesterol homeostasis in chronic viral hepatitis and HCC, including miR-21, miR-27, and miR-33. Last, we validated in human hepatoma cells that both miR-21 and miR-27 significantly repress cholesterol synthesis and that miR-27 does so in part through regulation of the gene that codes for the rate-limiting enzyme 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase (HMGCR). IMPORTANCE Hepatitis B virus (HBV) and hepatitis C virus (HCV) are phylogenetically unrelated hepatotropic viruses that persistently infect hundreds of millions of people world-wide, often leading to chronic liver disease and hepatocellular carcinoma (HCC). Chronic hepatitis B (CHB), chronic hepatitis C (CHC), and associated HCC often lead to cholesterol imbalance and dyslipidemia. However, the regulatory mechanisms underlying the dysregulation of lipid pathways in these disease states are incompletely understood. MicroRNAs (miRNAs) have emerged as critical modulators of lipid homeostasis. Here we use a blend of genomic, molecular, and biochemical strategies to identify key miRNAs that drive the lipid phenotypes of chronic viral hepatitis and HCC. These findings provide a panoramic view of the miRNA landscape in chronic viral hepatitis, which could contribute to the development of novel and more-effective miRNA-based therapeutic strategies.